Percutaneous Management of Postoperative Bile Leaks with an Ethylene Vinyl Alcohol Copolymer (Onyx) - Uller, W.; Müller-Wille, R.; Loss, M.; Hammer, S.; Schleder, S.; Goessmann, H.; Wiggermann, P.; Stroszczynski, C.; Wohlgemuth, W. A (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: The management of postoperative bile leakage is challenging especially if the leak rises from the cut surface of the liver and endoscopic treatment fails. Percutaneous transhepatic treatment of bile leaks with biliary drainage is accepted but often requires long-term placement of the drains and is associated with treatment failures. This series evaluates selective embolization of bile ducts with an ethylene vinyl alcohol copolymer (Onyx) in patients with postoperative bile leaks as an alternative treatment option.Materials and Methods: Between January and September 2012, five consecutive patients with persistent postoperative bile leaks underwent percutaneous transhepatic Onyx application and were analyzed regarding procedural management, complications and success rates.Results: The persistent bile leaks were situated at the cystic stump (after cholecystectomy, n = 2), at the cut surface of the liver (after extended liver resection, n = 2) and at the surface of the liver after surgical exploration and perihepatic abscess (n = 1). Bile drainage alone (endoscopic or percutaneous) failed in all patients and open redo-surgery was deemed potentially harmful. Bilomas were externally drained in all patients before Onyx application. For the closure of bile leaks, Onyx was injected through a microcatheter in a previously built coil nest to keep Onyx in place. All bile leaks were initially closed immediately. In the 2nd week after Onyx embolization, 2 patients showed recurrent small bile leaks without clinical symptoms. In the 4th week after Onyx application, all leaks were closed. No complications occurred.Conclusion: All leaking bile ducts were initially closed immediately after Onyx application. In the 2nd week after Onyx application, 2 patients showed small bile leaks without clinical symptoms. All leaks were closed in the 4th week after Onyx application. Key Points: Percutaneous treatment of postoperative bile leaks with Onyx seems to be an effective therapy if endoscopy fails and redo-surgery is deemed harmful.Citation Format:
Keywords: bile ducts; interventional procedures; percutaneous; PTC; PTBD; biliary leakage